Eggshell translucency in late-phase laying hens and its effect on egg quality and physiological indicators - Ren, He-Ling; Zhao, Xiao-Yu; Di, Ke-Qian; Li, Lan-Hui; Hao, Er-Ying; Chen, Hui; Zhou, Rong-Yan; Nie, Chang-Sheng; Wang, De-He (Frontiers in Veterinary Science, 2023)
Eggshell translucency severely affects external egg quality, and variations in the eggshell or eggshell membrane are considered the structural basis of the trait. Research has shown that 1.85% additional mixed fatty acids in the diet would greatly decrease the occurrence of eggshell translucency. Only a few studies have examined the phenotypic regularity of eggshell translucency with the increasing age of hens. Therefore, two strains, 1139 Rhode Island Red-White (RIR-White) and 836 Dwarf Layer-White (DWL-White), were used, and from each strain, 30 hens each that consecutively laid translucent or opaque eggs at 67 wks of age were selected. Subsequently, eggshell translucency, internal quality and external quality of eggs, and total cholesterol, albumin, calcium binding protein and other physiological indicators related to lipid, lipoprotein, and calcium metabolisms at the 75th, 79th, and 83rd wks of age in the late phase of the laying cycle were determined. Results: (1) In terms of flocks, for both strains, the translucency scores of the translucent groups were significantly higher than those of the opaque groups (P < 0.05); in terms of individuals, 81.1% RIR-White and 82.8% DWL-White hens consecutively laid eggs of the same or similar translucency, indicating the stability of the trait with increasing hen age; (2) In RIR-White, the eggshell strength of the translucent group at 75 weeks was significantly higher than that of the opaque group (P < 0.05); in DWL-White, the eggshell membrane thickness of the translucent group at the 75th and 83rd weeks was significantly lower than that of the opaque group (P < 0.05); (3) Compared to the opaque groups, the translucent groups had lower total cholesterol content in both RIR-White and DWL-White, lower albumin content in DWL-White at the 79th weeks (P < 0.05), and higher calcium-binding protein (CALB1) in RIR-White at the 83rd weeks (P < 0.05). In summary, this study illustrates the stability of eggshell translucency in late-phase laying hens and provides a reference of physiological indicators for exploring the formation of translucent eggs.